Uso de telas digitais na primeiríssima infância, sob a ótica de mães e profissionais - Brito, Paloma Karen Holanda (2022)
Introduction: The first years of a child’s life are crucial for brain development, which can undergo changes due to external stimuli, such as the use of digital screens. The growing appropriation of technologies causes an increase in the use of screens by children, requiring greater attention and caution from parents and professionals. Objectives: To understand the perception of mothers, as well as health and education professionals, about the use of digital screens in very early childhood and its effects on child development; to analyze the influence of this use on parental relationships; and to identify use in day care centers and health services. Methodological Pathway: Qualitative and exploratory-descriptive study, carried out in the city of Cajazeiras, Paraíba, Brazil, with mothers of children aged between zero and three years, as well as health and education professionals. Data were collected between July and October 2021 through interviews held in a virtual environment, using a semi-structured script. Data analysis followed the steps of Inductive Thematic Analysis and was based on Bronfenbrenner’s Bioecological Theory. The research project was approved by the Ethics Committee under opinion nº 4.736.257 and Certificate of Presentation for Ethical Appreciation nº 46539121.5.0000.518. Results: Screens are present in the daily routine of families and in day care centers and health services, being considered as a distraction tool for the child and facilitating element for pedagogical activities and childcare consultations. Its use is perceived as positive by some mothers and professionals, since it contributes to the learning and development of new skills, but it is also considered harmful, as it causes damage to the child’s cognitive, mental and social areas, in addition to harming parental relationships. Final Considerations: There were different perceptions about the use of screens and the ways of using them at home and in health and education services. Therefore, the awareness and dissemination of knowledge about digital screens and their effects on very early childhood are important strategies to foster healthy habits and to promote child development, as well as the strengthening of public policies focused children’s health.